POPULASI TIKUS DAN PENGETAHUAN MASYARAKAT TENTANG TIKUS DAN PENYAKIT YANG DITULARKANNYA DI KECAMATAN BERBAH, KABUPATEN SLEMAN - Nova pramestuti; Bina ikawati; Novia tri astuti (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2012)
Leptospirosis is a zoonotic disease transmitted by Leptospira bacteria by rats as the main reservoir . Cases of leptospirosis occurred in several districts in Sleman. One of them is Berbah Sub-district with one case of leptospirosis in 2011. The purpose of this study to identify the biotic and abiotic environmental conditions, species of rodents captured in the study site, trap success, and Leptospira bacteria in the blood serum and kidney of rats. The study was conducted in the Jogotirto Village, Berbah Sub-district, Sleman District. As many as 150 traps had been used in 2 trapped indoor and 2 trapped outdoor during 3 days. Measurements, observations environmental conditions and interviews about rats and rats disease transmission around leptospirosis cases. Rats had been trapped identified, blood and kidneys was taken to be examined in the presence of Leptospira bacteria by using PCR (Polymerase Chain Reaction). Data were analyzed descriptively in tables and graphs. Biotic and abiotic environmental conditions favor transmission of leptospirosis. Rats spesies had been found were Rattus tanezumi, Suncus murinus, and R. tiomanicus with trap succes indoor as much 10.5% and outdoor as much 5.2%. People had less knowledge about rats and rats disease transmission.